Basis for Judges' Considerations in Decisions on Persecution Cases - Putri Alya Zalsabila Hasan (Estudiante Law Journal, 2021)
This study aims to determine the basis of the judge's decision in the case of persecution. The research method used by the author in this study is normative research. The research approach uses analytical descriptive and uses qualitative analysis techniques. The results of this study indicate that the basis for the judge's consideration is three things, namely legal facts, evidence and the judge's belief. These three things will make the judge in terms of giving decisions to the perpetrators of criminal acts or in this case the defendants. These three points have been contained in the indictment of the public prosecutor which will then be concluded and analyzed by the judge to convince his heart in terms of imposing sanctions in accordance with what the defendants did. What should be mitigating for the Defendant in the form of the Defendant promising not to repeat his actions should not be used as consideration for the Judge in deciding a case. This could have been a pretense to gain sympathy from the Judge. So the consideration must be focused on the actions committed by the defendants